Pengembangan Media Pembelajaran Interaktif Berbasis Wordwall Pada Pembelajaran IPAS Kelas IV Sekolah Dasar - Jathy, Rekka Oktania Handoyo; Priyanto, Wawan; Purnamasari, Iin (Diniyah: Jurnal Pendidikan Dasar, 2024)
This study aims to develop an interactive learning medium based on Wordwall for teaching IPAS (Science and Social Studies Integration) with the topic of Indonesia's cultural richness for fourth-grade elementary school students. The background of the study is the low student engagement and understanding of IPAS material when delivered through conventional methods. This research used a Research and Development (R&D) method with the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. Validation was conducted by media and content experts, and trials for practicality and effectiveness were carried out in two elementary schools. The results showed that the Wordwall-based interactive learning media was deemed highly feasible, with a media validation score of 98% and content validation of 88.75%. The media’s practicality was rated as highly practical by teachers (86.25%) and students (93.2%). Furthermore, the paired sample t-test revealed a significant improvement in students’ learning outcomes after using this media. These findings indicate that Wordwall-based media enhances student engagement and understanding of IPAS material in a fun and interactive way. This study contributes to the provision of contextual, innovative, and culturally relevant learning media and opens avenues for further research on different topics and educational levels.Keywords: Interactive learning media, wordwall, IPAS, Indonesian cultural richness, elementary school, educational games, local wisdom